ISLAMIC PSYCHOPEDAGOGY IN INCLUSIVE EDUCATION AT BAHARI SPECIAL SCHOOL OF LABUAN PANDEGLANG - Aat Royhatudin (Cakrawala Pedagogik, 2023)
Children with special needs in the context of empirical facts have different physical and mental, so that psychlogically treated differently in general, it is necessary inclusion education with a press point on two things namely personality and character are specifically discussed using Islamic Psychopedagogical approach. The purpose of this study is how Islamic psychopedagogy can be implemented by educators and parents in the Special School of Bahari Labuan, then it can be absorbed by children with special needs who are assumed to be very weak in academic due to physical limitations. This qualitative research method reveals a certain meaning or understanding, with observational data collection techniques and in-depth interviews and then analyzed descriptively with Islamic psychopedagogical approach conducted to educators and parents of children with special needs in special schools nautical Labuan. The results showed that with inclusion and open services, psychologically, pedagogically and Islamic values to educators and parents are then understood and implemented by educators at school and parents at home, the character of children with special needs is more easily recognized from attitudes and behaviors, such as impaired learning ability in children, impaired emotional and interacting ability in children and other ability disorders in children can be overcome with Islamic Psychopedagogical design, especially in inclusive education.